A three-dimensional magnetic field sensor based on a single spin–orbit-torque device via domain nucleation - Guo, Zhe; Li, Ruofan; Zhang, Shuai; Tian, Yufeng; Hong, Jeongmin; You, Long (Applied physics letters, 2022)
Detecting a three-dimensional (3D) magnetic field by a compact and simple structure or device has always been a challenging work. The recent discovery of 3D magnetic field sensing through the single spin–orbit torque device consisting of the Ta/CoFeB/MgO heterostructure, based on the domain wall motion, offers a revolutionary way to tackle this problem. Here, we demonstrate a 3D magnetic field sensor based on the W/CoFeB/MgO heterostructure via domain nucleation dominated magnetization reversal. In such a heterostructure, the in-plane (IP) and out-of-plane (OOP) magnetic field components drive the grains reversal with different manners, enabling the distinguishment of the contributions from IP and OOP components. The linear modulations of anomalous Hall resistance by x, y, and z components of magnetic fields have been obtained, respectively, with the same linear range of −20 to +20 Oe for each component. Typically, a higher linearity is realized in this work compared with the previous domain wall motion based sensor, which is a critical characteristic for the magnetic field sensor.